Characterization and Functional Properties of Electroplated Silver and Silver Alloys from Cyanide Free Electrolytes - Orecchioni, Quentin; Gigandet, Marie-Pierre; Bedjou, Walid; Tardelli, Joffrey; Hihn, Jean-Yves (Meeting abstracts (Electrochemical Society), 2024)
The reduction of tungstate ions in aqueous solution is often referred as induced codeposition. Those ions can only be reduced to a metallic state alongside another element which is mostly nickel. However, other metal such as cobalt and iron are reported in the literature. Various hypothesis have been made concerning the precise mechanism behind induced codeposition, but even if the exact role of the various chemical species isn’t fully understood, tungsten was successfully electrodeposited using more noble element such as copper and silver [1]. Silver electroplating is a widely used process in the connector industry. In fact, while silver coatings exhibit an extremely high thermal and electrical conductivity, they remain highly vulnerable to sulphuration and present poor mechanical properties both in hardness and wear resistances. For these reasons, electrodeposition of silver alloys has aroused a recent interest, relying on an alloying element addition that would compensate silver weaknesses. Alloy compounds inducing high mechanical and chemical resistances such as tungsten, are obvious candidates. Moreover, limitations in free cyanide use in electroplating processes is an active research subject. While gold-cyanide complexes are stable enough to be used without any cyanide ions in solution, silver complexation in alkaline baths is highly dependent on high free cyanide concentrations. Processes using thiosulfate, nitrogen heterocyclic compounds or methane sulfonate were proposed as replacement solutions, but they are still under investigations [2]. The present study is part of the SILAHPERF project, led by IRT-M2P and UTINAM Institute, which try to investigate the codeposition mechanism of various silver-based alloys of interest with a particular focus on silver-tungsten while seeking for environmental-friendly solutions. A cyanide-free silver-tungsten plating bath is proposed and resulting coatings are characterized by various techniques (SEM, XRD, GDOES...). Resolutely intended for connector applications, functional properties such as hardness, wear resistance and electrical conductivity of the deposit were evaluated depending on bath composition and electrolysis parameters. [1] A. Kola, X. Geng, and E. J. Podlaha, ‘Ag–W electrodeposits with high W content from thiourea–citrate electrolytes’, Journal of Electroanalytical Chemistry , vol. 761, pp. 125–130, Jan. 2016 [2] B. Satpathy, S. Jena, S. Das, and K. Das, ‘A comprehensive review of various non-cyanide electroplating baths for the production of silver and gold coatings’, International Materials Reviews , vol. 68, no. 7, pp. 825–861, Oct. 2023